Analisis Retorika Visual dan Sentimen Analisis pada Kampanye Ganjar Pranowo di dalam Video Adzan Magribh - Gagas Ezhar Rahmayadi; Deny Haryadi; R. Bhima Danniswara; Valentino Kenny Surjadi; Netanel Danur Wendra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Campaigns are a form of communication used by politicians to gain support. According to theory, campaigns are persuasive communications aimed at changing the behavior of the communicant as the message recipient. The choice of media in conducting campaigns is an important factor. The role of media will strengthen the communication concept so that the message conveyed can be interpreted according to the goal. In the 2024 presidential campaign, one of the presidential candidates, Ganjar Pranowo, used television advertisements, specifically the Maghrib call to prayer, as part of his campaign strategy. The method used in this research employs a qualitative approach. Visual Rhetoric Theory is used to interpret the message in the video. Additionally, supporting sentiment analysis theory is used to analyze the research subject, namely the public who have seen the video. Public responses were taken from social media comments. Thus, the results of the analysis from both theories are combined into one conclusion. The result is that Ganjar Pranowo made a fairly good impression, but it is not perfect. There are still some errors in the video that raise questions about Ganjar Pranowo's credibility.